Birds Records from Danjugan Island Negros Occidental, Philippines - King, Tony; Tyler, Simon; Turner, Craig; O'Malley, Roger; Raines, Peter (Silliman Journal, 2022)
The bird fauna of Danjugan Island, which forms part of one of the most globally threatened Endemic Bird Areas (EBA 152), was recently surveyed as part of a wider biodiversity survey program completed by Coral Cay Conservation and the Philippine Reef and Rainforest Conservation Foundation, Inc. Observations were made over a four-month period in 2001 and a number of species of conservation interest were recorded. Species found to be breeding on the island included Rufous Night-heron (Nycticorax caledonicus), Tabon Scrubfowl (Megapodius cuiningii), White-bellied Sea-eagle (Haliaeetus leucogaster), and Black-naped Tern (Sterna sumatrana). Species endemic to the Philippines included Black-chinned Fruit-dove (Ptilinopus leclancheri), Philippine Hawk-owl (Ninox philippensis), and Philippine Leaf-warbler (Phylloscopus olivaceus). Several migrant species, such as Red-necked Phalarope (Phalaropus lobatus) and Blue Rock-thrush (Monticola solitarius), were recorded on dates as early as any previous records from the Philippines. These preliminary results highlight the importance of the island as a refuge for a diverse avian fauna, and in light of the island's protective designation, locally-focused conservation and research recommendations are proposed.